Estrogen regulates the tumour suppressor MiRNA-30c and its target gene, MTA-1, in endometrial cancer. - Xiangyi Kong (Public Library of Science (PLoS), 2014)
MicroRNA-30c (miR-30c) has been reported to be a tumour suppressor in endometrial cancer (EC). We demonstrate that miR-30c is down-regulated in EC tissue and is highly expressed in estrogen receptor (ER)-negative HEC-1-B cells. MiR-30c directly inhibits MTA-1 expression and functions as a tumour suppressor via the miR-30c-MTA-1 signalling pathway. Furthermore, miR-30c is decreased upon E2 treatment in both ER-positive Ishikawa and ER-negative HEC-1-B cells. Taken together, our results suggest that miR-30c is an important deregulated miRNA in EC and might serve as a potential biomarker and novel therapeutic target for EC.